Beyond subsidiarity: the indirect effect of the Early Warning System on national parliamentary scutiny in European Union affairs. Issue 3 (9th March 2017) - Miklin, Eric
ABSTRACT: The Early Warning System (EWS) introduced with the Lisbon Treaty allows national parliaments to directly intervene in European Union (EU) decision-making for the first time. Most scholars expected participation in the EWS and the system's impact to be modest, though, as the instrument provides parliamentary parties with little added value from a policy- or vote-seeking perspective. Running counter to that view, this article argues that parliaments are under normative pressure to engage in the EWS, which may have significantly increased the attention and resources they devote to EU issues. By triggering policy learning, this again may have improved parliamentary attempts to actively shape EU decision-making more generally and beyond subsidiarity. I expect both effects to be especially strong on chambers that had been comparatively inactive in EU scrutiny before Lisbon. The arguments' plausibility is demonstrated through a study of post-Lisbon changes in the Austrian Nationalrat and the Dutch Tweede Kamer.